Evaluating current sensing methods for accurate characterization in small chip size SiC MOSFETs - Y. Kim; H. Park; S. Yoon; H. Kang (Power Electronic Devices and Components)
Wide Bandgap power devices, such as SiC MOSFETs, offer superior switching performance, making them essential in high-frequency power systems. This study compares two current sensing methods—Coaxial Shunt Resistor (CSR) and Split-Core Current Probe (SCP) and evaluates their impact on switching characterization of small chip size SiC MOSFETs using Double Pulse Tests. The CSR, with up to 1 GHz bandwidth, enables more accurate transient current measurement compared to the 100 MHz-SCP. Experimental results show that at a high current density, the CSR method at 1 GHz reduced turn-on switching loss by up to 52.4 % and turn-off switching loss by up to 19.8 % compared to the SCP method. Conversely, at low current density, the CSR method captured 74.4 % higher Eon due to its finer resolution of high frequency transients, not detected by SCP. These results reveal that high bandwidth CSR sensing is critical for accurately and reliably characterizing fast switching small chip size SiC MOSFETs.